Gender Discourse on Social Media: A Systematic Synthesis Toward a Conceptual Model of Ideology, Performativity, and Platform Political Economy - Aliyah Aliyah; Zainal Rafli; Miftahulkhairah Anwar (CV Wahana Publikasi, 2026)
Social media has transformed how gender issues are created, circulated, and contested in the digital public sphere, yet studies synthesizing gender discourse themes across platforms, cultural contexts, and theoretical perspectives remain limited, as most empirical research focuses on specific issues, communities, or individual platforms. This fragmentation has resulted in insufficient understanding of how ideological formations, gender performativity, and platform mechanisms interact in shaping contemporary digital gender meanings. This study aims to identify the dominant themes and patterns in gender discourse on social media and to develop a Conceptual Model of Ideology, Performativity, and Platform Political Economy (IPP Model) through systematic literature synthesis. The study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 Statement (Page et al., 2021) and thematic synthesis methodology (Thomas & Harden, 2008), applied to thirteen international peer-reviewed articles on gender discourse in social media published in 2026. The findings reveal four interdependent themes shaping the production, circulation, and legitimation of gender meanings in digital spaces: ideological polarization, gender performativity, body politics, and platform economy. Based on these findings, the study proposes the IPP Model as an integrative analytical framework explaining gender discourse as the outcome of interactions among ideological systems, multimodal performative practices, embodied representations, and algorithmically governed platform infrastructures. The model contributes to digital discourse analysis, multimodal studies, applied linguistics, and gender studies by repositioning social media from a passive communication medium into an active socio-technical actor that shapes the visibility, circulation, and legitimacy of gender meanings.